Holla Churros - Azmi, Mohamad Izzat Amar; Ismail, Abdul Halim; Zakaria, Nur Amni; Suhaimi, Muhammad Alif Izuddin; Rusli, Nur Azlin; Mohamad Kamaruddin, Hairil Azfar (2015)
Business plan is written documents which describe the purposed business to be undertaken in the comprehensive manner. It is also known as a project paper, working paper, business proposal or prospectus. This business plan is also drafted so that HOLA Churros can get financing to start its business. The financing will be used to start up its asset like kitchen equipment, furniture and fittings, advertising. We can get all this from trusted supplier, and they agreed to provide us with those assets. We can also use this guideline to the manager in order to success in the business. HOLA Churros and our entire partner have set our goal and path to gain profit as we have planned. This business plan includes our company background, marketing strategy, operational plan, sales forecast, and the financial plan of the business. HOLA Churros will utilize the entire asset so that we can maximize the profit. The profit will be used to generate more profit in the long term objective and pay loan to Bank Islam including the interest in the loan given. Hopefully this plan can be used to convinced the business achieve the target and gift a good profit.